The glocalization of personal ethical threshold: an extension study on eastern context - Setyabudi Indartono; Chun-Hsi Vivian Chen (JOURNAL OF EDUCATION, 2008)
Abstract: This paper extends the previous study of Debra R Comer and Vega publish at Journal of business ethics in 2008, which investigated 506 students representing eight business schools throughout the United States. Recent study tried to investigate more, in case to Indonesia and Taiwan context. The present study is aimed at finding out whether personal ethical threshold (TEP) applies to Indonesian and Taiwanese students. A total of 545 students from Indonesia and Taiwan were involved in the data collection. Confirmatory factor analysis (CFA) was used for factor loading and six fit models were used for measurement of overall fits. Research findings indicate that (1) school status has correlation with ethical thresholds; (2) for Taiwanese students, gender correlates significantly (r. = …, p. = …); and the over-all fit of model is fair (stat).Keywords: personal ethical threshold (TEP), individualist cultures, collective cultures, glocalization, business ethics, regional contexts, moral intensity